THE INFLUENCE OF CONFORMITY AND LIFE SATISFACTION ON FEAR OF MISSING OUT (FOMO) AMONG STUDENTS OF MUHAMMADIYAH 2 SENIOR HIGH SCHOOL SIDOARJO - Aisyah Putri Juniarga; Nastiti, Dwi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the simultaneous and individual effects of conformity and life satisfaction on Fear of Missing Out (FoMO) among students at Muhammadiyah 2 Senior High School Sidoarjo. Method: Employing a correlational quantitative design, the study involved 270 students selected from a population of 1,146 using accidental sampling. Data were collected using validated scales for conformity (α = 0.860), life satisfaction (α = 0.807), and FoMO (α = 0.898). Data analysis was conducted using multiple linear regression with the JASP statistical software. Results: The findings indicate that conformity and life satisfaction simultaneously have a significant influence on FoMO (F = 57.363, p < 0.001). Individually, conformity positively and significantly influences FoMO (t = 3.289, p = 0.001), while life satisfaction has a significant negative influence on FoMO (t = -9.553, p < 0.001), suggesting that higher life satisfaction is associated with lower levels of FoMO. Novelty: This study contributes new insights into the psychological mechanisms underlying FoMO among adolescents by highlighting the dual role of social conformity and subjective well-being, particularly within the context of Indonesian high school students.